Robot-Assisted Radical Prostatectomy Using the KangDuo Surgical Robot-01 System: A Prospective, Single-Center, Single-Arm Clinical Study. Issue 1 (18th July 2022) - Fan, Shubo; Zhang, Zhongyuan; Wang, Jie; Xiong, Shengwei; Dai, Xiaofei; Chen, Xu; Li, Zhihua; Han, Guanpeng; Zhu, Jun; Hao, Han; Yu, Wei; Cui, Liang; et al.
Abstract : Purpose: Our goal was to evaluate the feasibility, safety and effectiveness of the KangDuo Surgical Robot-01 (KD-SR-01) system for robot-assisted radical prostatectomy (RARP). Materials and Methods: This prospective, single-center, single-arm clinical study was conducted from May 2021 to August 2021. Sixteen RARP procedures with the KD-SR-01 system were performed by 1 surgeon. The perioperative and followup data were prospectively recorded. Early oncologic outcomes were assessed according to surgical margin status and continence was defined as no more than 1 pad daily or urine leakage of ≤20 gm by the 24-hour pad weight test. Ergonomics were assessed with the NASA-TLX (National Aeronautics and Space Administration Task Load Index). Results: All cases were completed successfully without conversion to traditional RARP, laparoscopic surgery or open surgery. The median docking time, console time and urethrovesical anastomosis time were 5.9 (range, 2.5–11.5), 87 (range, 70–120) and 14.4 minutes (range, 12.0–25.7), respectively. The median estimated blood loss was 50 ml (range, 10–200). None of patients required intraoperative transfusion. The median postoperative hospital stay was 5 days (range, 4–10). Overall, a positive surgical margin occurred in 4 (25%) patients. No biochemical recurrence occurred within 1 month after surgery. The continence rate was 87.5% (14/16) at 1 month after catheter removal. No severe intraoperative or postoperative complications (Clavien–Dindo grade ≥3) occurred. The surgeon reported a high comfort level with a NASA-TLX global score of 22.7±3.2. Conclusions: The KD-SR-01 system is feasible, safe and effective for management of localized prostate cancer.